Dietary And Lifestyle Factors Associated With Risk Ofcolorectal Adenoma In Patients At Hospital Kuala Lumpur - Ramadas, Amutha (2006)
Cancer is now the third leading cause of death in Malaysia and one in four Malaysians is at risk of developing cancer. In Peninsular Malaysia, there was a slight decline in percentage of colon (-0.2%) and rectal (-0.2%) cancer incidence in males in the year 2003 compared to the previous year as reported by National Cancer Registry (2004). Yet, there was an increase in percentages of these cancer incidences in women (+0.4% in colon cancer and +0.7% in rectal cancer). Colorectal cancers are thought to develop over a period of several years, and most of them develop from benign, neoplastic adenomatous polyps (Bond, 2000). Colorectal adenomas have been shown, but not always, significantly related to various dietary and lifestyle factors. These factors have yet to be reported in relation to colorectal polyps in the Malaysian population. This case-control study was carried out to determine the relationship between dietary and lifestyle characteristics, and risk for colorectal adenomas among Malaysians. After screening for inclusion and exclusion criteria, 11 8 men and women with good cognition and who were at least 30 years at the time of interview and have undergone colonoscopy in Hospital Kuala Lumpur were enrolled in the this study upon obtaining ethical clearance. Fifty nine patients diagnosed with colorectal adenomas were recruited as case subjects, while a similar number of patients diagnosed negative for any polyps were recruited as controls. A structured and pre-tested interviewer administrated questionnaire was used for data collection. The fasting blood samples were collected by trained and qualified nurse, and analyzed using relevant analysis in the laboratory. The collected data were then analyzed with SPSS version 12.0. Multivariate analysis concluded that the higher servings of fruits (adjusted OR = 0.150, 95% CI = 0.052 - 0.434) and vegetables (adjusted OR = 0.344, 95% CI = 0.149 - 0.794), crude fibre intake (adjusted OR = 0.659, 95% CI = 0.481 - 0.905) and plasma levels of total cholesterol (adjusted OR = 5.370, 95% CI = 1.861 - 15.495), LDL (adjusted OR = 1.093, 95% CI = 1.022 - 2.386) and vitamin E (adjusted OR = 0.481, 95% CI = 0.306 - 0.758) found to significantly contribute to the risk for colorectal adenomas, upon adjusting for potential covariates. A larger study and possibly a prospective study which recruits study subjects from various places in Malaysia will be an excellent effort to confirm these findings. Interventions with focuses on behavioural change may be able to reduce one's risk for colorectal adenomas which in the long-term reduce hisher risk for developing colorectal cancer in the future.